Green finance as a tool to stimulate investments in environmentally sustainable projects - U. S. Karimov (Вестник университета)
This article discusses one of  the most effective methods of  financing investments in  fixed assets through loans or   bonds. The mechanism of   green financing is a   tool that can attract part of   the necessary investments to   achieve ambitious goals of   the designated strategy. The ESG (environmental, social, governance) agenda has recently become one of  the most popular and widely discussed topics in   global communities, including financial ones, as   any transformation and change in   business and economic conjunctures often require a   significant amount of   investment. The largest number of   questions is   raised by   the E  (environmental) component which is   responsible for ecology, namely for ensuring decarbonisation of   economic and social processes as   well as  for adapting to   the challenges associated with the global energy transition, for protecting and multiplying natural capital, and reducing the harmful human impact on   the environment. The article also provides a   methodology for calculating the greenium that investors are willing to   pay the issuer. The main attention is   paid to a   detailed analysis of   the current state of   the green bond market and to   the process of   forming a   greenium in   the Russian green finance market which will help investors make informed decisions when choosing investments.